The Effect of Brisk Walking Exercise on Blood Pressure in Hypertensive Patients in Karanganyar Village, Sambungmacan District - Zalika Hilwa Safitri; Dwi Lestari Mukti Palupi; Muzaroah Ermawati Ulkhasanah (Universitas Duta Bangsa Surakarta, 2026)
Introduction : Hypertension is a chronic condition characterized by elevated blood pressure, specifically systolic blood pressure ?140 mmHg and diastolic blood pressure ?90 mmHg. The condition is often referred to as the “Silent Killer” because it typically does not present with obvious symptoms, leading many individuals to remain unaware that they have hypertension. If left untreated, hypertension increases the risk of heart disease, stroke, and other cardiovascular conditions. One non-pharmacological approach to hypertension is Brisk Walking Exercise. Objectives : To determine the effect of Brisk Walking Exercise on blood pressure in hypertensive patients in Karanganyar Village, Sambungmacan Subdistrict. Methods: : This study used a Pre-Experimental design with a one-group pre-test post-test approach. The sample consisted of 40 respondents from a population of 450 individuals, selected using purposive sampling. The measurement tool used was a digital sphygmomanometer, and data analysis was performed using the Wilcoxon Signed Ranks-Test. Results: The majority of respondents were aged 60-74 years (67.5%), the majority were female (87.5%), and the majority were farmers (57.5%). Blood pressure after the Brisk Walking Exercise intervention showed an average decrease in systole blood pressure of 24.85 mmHg (from 162.50 mmHg to 137.65 mmHg) and a decrease in diastole blood pressure of 5.7 mmHg (from 87.15 mmHg to 81.45 mmHg). There was a significant decrease in blood pressure with a z -7.772 to -7.771, p-value 0.000 (? <0.05). Conclusions: Brisk Walking Exercise performed regulary three times a week for 30 minutes has been proven effective in lowering blood pressure in hypertensive patients.